Analisis Semantik Pada Puisi "Sajak Matahari" Karya W.S Rendra - Angelina Gracia Ginting; Dear Ezra Sipayung; Sri Hartati Sinaga; Yuliana Sari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Poetry is a literary work that is produced from someone's experiences. A poem is composed using beautiful language and meaningful words written in the form of verses. To understand the meaning conveyed in a poem, semantic analysis needs to be conducted. Semantics is a branch of linguistics that discusses meaning and significance. Therefore, this study aims to analyze the meanings contained in W.S. Rendra's poem titled "Sajak Matahari" (The Sun Poem). Semantic analysis in this study is focused on analyzing lexical meaning, referential meaning, grammatical meaning, and figurative meaning. The method used in this study is qualitative descriptive method. The qualitative descriptive approach will allow researchers to analyze the details of meaning in the poem to explain the meaning more deeply. In collecting research data, researchers use reading and note-taking techniques. The reading technique is carried out by reading the contents of the poem, then the results of reading the poem to examine the meaning. Note-taking technique is used to record lexical, referential, grammatical, and figurative meanings. The result of the meaning analysis in the poem "Sajak Matahari" is a poem that discusses perseverance/call for creating change in society, thus creating a fair and peaceful situation.